Pengaruh Media Booklet dan Audio Visual terhadap Pengetahuan Akseptor KB tentang Kontrasepsi Jangka Panjang di Wilayah Bogor Utara Tahun 2023 - Cucu Supriatin; Dewi D. Korawati; Kristina Dewi Yanti; Patimah Patimah; Samsiah Samsiah (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Long-acting contraception is one effective method of family planning. However, sufficient knowledge about long-acting contraception is still low among birth control acceptors in the North Bogor Region. Therefore, this study aims to investigate the effect of the use of booklet and audio-visual media on the knowledge of birth control acceptors regarding long-term contraception in the region. The purpose of this study was to evaluate whether the use of booklet and audio-visual media can increase the knowledge of family planning acceptors about long-term contraception in the North Bogor Region. This study used a pseudo-experimental design with a control group pretest-posttest design. The study sample consisted of 100 KB acceptors selected by purposive sampling and divided into two groups, namely the experimental group that received intervention using booklet and audio-visual media, and the control group that did not receive the intervention. The study data were collected through knowledge questionnaires before and after the intervention. Data analysis was performed using independent t-test and t-paired test. The results showed that there was a significant increase in knowledge of birth control acceptors after receiving interventions using booklet and audio-visual media. The experimental group showed a higher increase in knowledge compared to the control group, in the treatment group with audiovisual media the increase in knowledge was better when compared to the health education control group with Booklet media The average level of knowledge of the control group before being given treatment was 12.5 After being given treatment the average score of the control group rose to 13.4. While the average Audio visual group average score was 13.25. After being treated, the average score increased by 14.6. The t-test result shows a p value (0.000<0.05). The use of booklet and audio-visual media is effective in increasing the knowledge of birth control acceptors about long-acting contraception.